Application of Augmented Reality in Animal Classification Based on Type of Food - Regan, Steve (Fakultas Komputer - Universitas Universal, 2024)
This study aims to design Augmented Reality (AR)-based learning media in animal classification based on their food types for elementary school students in Maitreyawira. By using Unity and Vuforia, this AR application is expected to provide an interactive and interesting learning experience for students. The method used in this study is the Multimedia Development Life Cycle (MDLC). The development process begins with the conceptualization stage, where an analysis of learning media needs is carried out through literature studies, interviews with teachers and students, and field observations. The results of the analysis are used to design the system and determine the specifications of the application to be developed. At the material collection stage, information regarding animal classification based on their food types is collected from various literature sources and interviews with biologists. The learning media creation stage is carried out using Unity as the main development platform and Vuforia for the implementation of AR technology. Testing is carried out to ensure that the application functions properly and meets user needs. Feedback from users, namely teachers and students. The results of this study are an AR application that can help students understand animal classification based on their food types more interactively and interestingly. This application is expected to increase students' interest and understanding of biology material, as well as provide a positive contribution to the learning process at Elementary School Maitreyawira.